2020
DOI: 10.1021/acsanm.0c02079
|View full text |Cite
|
Sign up to set email alerts
|

N-Doped Graphene Nanoplatelets for Direct Capsaicin Detection in Chili Pepper Samples

Abstract: In this study, we have designed and fabricated a portable electrochemical sensor for direct detection of capsaicin in chili samples at the point-of-testing. The sensor, shaped like a chili pepper and highly portable, is essentially a disposable electrochemical paper-based analytical device (ePAD) modified with N-doped graphene nanoplatelets (GrNPs). The sensor consists of three components: (i) a small potentiostat device, (ii) an interface allowing connection to a smartphone for monitoring and control, and (ii… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 36 publications
0
13
0
Order By: Relevance
“…Furthermore, the oxygen-containing functional groups information on the GCE surface before and after electrochemical pretreatment in sulfuric acid was characterized by the FT-IR technique, as shown in Figure 2 E. Before GCE electrochemical pretreatment ( Figure 2 E-a), small peaks at 2921, 2860, and 1621 cm −1 , which attribute to stretching band of -C-H and C=C in the structure of carbon material were observed [ 18 , 35 ], indicating a less functional group on the pristine GCE surface. In contrast, after GCE was electrochemically pretreated in sulfuric acid at 1.8 V ( Figure 2 E-b), stretching bands were more pronounced than pristine GCE, which can be observed in the bands of the oxygen-containing functional groups in the region of 1800 to 700 cm −1 , which can be assigned to -C=O, -C=C, -COO − , -C-O-C, and C-C stretching bands and -OH bending modes in ether, lactones, carboxyl, and phenolic structures [ 15 , 18 , 33 ]. The strong intensities of those bands after electrochemical pretreatment of GCE in sulfuric acid confirmed that the oxygen-containing functional groups were successfully functionalized on the GCE surface during electrochemical pretreatment [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the oxygen-containing functional groups information on the GCE surface before and after electrochemical pretreatment in sulfuric acid was characterized by the FT-IR technique, as shown in Figure 2 E. Before GCE electrochemical pretreatment ( Figure 2 E-a), small peaks at 2921, 2860, and 1621 cm −1 , which attribute to stretching band of -C-H and C=C in the structure of carbon material were observed [ 18 , 35 ], indicating a less functional group on the pristine GCE surface. In contrast, after GCE was electrochemically pretreated in sulfuric acid at 1.8 V ( Figure 2 E-b), stretching bands were more pronounced than pristine GCE, which can be observed in the bands of the oxygen-containing functional groups in the region of 1800 to 700 cm −1 , which can be assigned to -C=O, -C=C, -COO − , -C-O-C, and C-C stretching bands and -OH bending modes in ether, lactones, carboxyl, and phenolic structures [ 15 , 18 , 33 ]. The strong intensities of those bands after electrochemical pretreatment of GCE in sulfuric acid confirmed that the oxygen-containing functional groups were successfully functionalized on the GCE surface during electrochemical pretreatment [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Developed analytical methods for the detection of alprazolam include high performance liquid chromatography [ 7 ], gas chromatography [ 8 ], UV-vis spectroscopy [ 9 ], and electrochemical techniques [ 10 , 11 , 12 ]. Electrochemical techniques are simple, inexpensive, and provide fast response times and good sensitivity [ 13 , 14 , 15 , 16 , 17 ]. Adsorptive stripping voltammetry (AdSV) is an electrochemical technique that is widely used for the analysis of trace organic compounds and various elements [ 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, efforts to develop cost-effective, fast, and direct detection of capsaicinoid content from samples using different techniques, such as voltammetry and near-infrared spectroscopy, have been made ( Crapnell and Banks, 2021 ). For example, a graphene-based portable device that can be connected to a smartphone has been developed and high accuracy and collinearity between the SHU values derived from the machine and from spectroscopy were observed ( Soleh et al, 2020 ). A colorimetric approach using the Gibbs reagent has also been employed for the rapid determination of capsaicinoid content and has a high correlation with HPLC ( Ryu et al, 2017 ).…”
Section: Phenomics and “Speed Breeding” To Accelerate Chile Pepper Im...mentioning
confidence: 99%
“…25 Until now, various catalytic materials, including boron-doped diamond, 26 carbon-based disposable electrodes, 27,28 metal nanoparticles (Ag/Ag 2 O, CeO 2 , Ru, Sn etc. ), [29][30][31][32] mesoporous cellular foams 33 and recently, N-doped atom graphene nanoplates 34 have been explored for selective and sensitive electrochemical determination of capsaicin. However, the synthesis of these catalysts is a time consuming, complicated procedure that requires harsh conditions and high temperature, and low stability and high cost are major concerns.…”
Section: Introductionmentioning
confidence: 99%